A retrospective study comparing percutaneous and open pedicle screw fixation for thoracolumbar fractures with spinal injuries. Issue 38 (September 2017) - Wang, Bowen; Fan, Yong; Dong, Jingjing; Wang, Hu; Wang, Faqi; Liu, Zhichen; Liu, Haoyuan; Feng, Yafei; Chen, Fengrong; Huang, Zheyuan; Chen, Ruisong; Lei, Wei; et al.
Abstract: Background: The purpose of this study was to evaluate the effectiveness between percutaneous and open pedicle screw fixation for treating thoracolumbar fractures with spinal injuries. Methods: A total of 105 patients with thoracolumbar fractures and spinal injuries were divided into a percutaneous pedicle screw fixation (PPSF) group with 56 patients, who underwent percutaneous pedicle screw fixation, and an open pedicle screw fixation (OPSF) group with 49 patients, who underwent open pedicle screw fixation in accordance with the treatment project. Relative operation indexes, radiologic, and effectiveness parameters were assessed and compared between the 2 groups. Results: Demographic and clinical features including age, body mass index, gender, fracture level, fracture classification, and Frankel grade in both groups were not significantly different (all P >.05). The PPSF group exhibits significantly lower operation time, intraoperative blood loss, postoperative drainage volume, and hospital stay on average compared with the OPSF group (all P  < .05). Besides, the average postoperative radiologic parameters, including Cobb angle (CA), vertebral wedge angle (VWA), vertebral front height percentage (VFHP), and sagittal index (SI), in both the groups were not significantly different (all P  > .05). Nevertheless, both visual analogue scale (VAS) and Oswestry disability index (ODI) after surgery decreased more substantially in the PPSF group than in the OPSF group (all P  < .05) while no significant difference in VAS scores or ODI during the last follow-up period was demonstrated in both the groups (both P  > .05). Frankel classifications were stimulated in both the groups during the last follow-up period. Conclusion: PPSF has a smaller incision, less intraoperative blood loss, shorter recovery time, higher safety measures on average compared with OPSF with respect to managing thoracolumbar fractures with spinal injuries.